Transcranial Doppler Ultrasonographic Evaluation of Cerebrovascular Abnormalities in Children With Acute Bacterial Meningitis - Fonseca, Yudy; Tshimanga, Taty; Ray, Stephen; Malhotra, Helen; Pongo, Jean; Bodi Mabiala, Joseph; Gushu, Montfort Bernard; Phiri, Tusekile; Chikaonda, Bertha Mekiseni; Ambitapio Musungufu, Davin; Uchama, Mananu; O'Brien, Nicole Fortier (Frontiers in Neurology, 2021)
Introduction- Bacterial meningitis (BM) is a global public health concern that results in significant morbidity and mortality. Cerebral arterial narrowing contributes to stroke in BM and may be amenable to intervention. However, it is difficult to diagnose in resource limited settings where the disease is common. Methods- This was a prospective observational study from September 2015- December 2019 in Sub-Saharan Africa. Children 1 month to 18 years of age with neutrophilic pleocytosis or a bacterial pathogen identified in the cerebrospinal fluid were enrolled. Transcranial Doppler ultrasound (TCD) of the middle cerebral arteries to identify flow abnormalities consistent with narrowing was performed daily. Results- Forty-seven patients were analyzed. The majority had Streptococcus pneumoniae (36%) or Neisseria meningitides (36%) meningitis. Admission TCD was normal in 10 (21%). High flow with a normal pulsatility index (PI) was seen in 20 (43%) and high flow with a low PI was identified in 7 (15%). Ten (21%) had low flow. All children with a normal TCD had a good outcome. Patients with a high-risk TCD flow pattern (high flow/low PI or low flow) were more likely to have a poor outcome (82% vs 38%, p=0.001). Conclusions- TCD can be used to evaluate the neurovasculature of children with BM and identify those at high risk of poor neurological outcome.